Budgetary impact of oral chemotherapy incorporation in Brazil: a real world data analysis from the private payer perspective - Clark, Otávio; Alves, Anna Flávia; Castro, Ana Paula; Santos, Fábio; Faleiros, Eneas; Clark, Luciana; Paladini, Luciano; Engel, Tobias; Pegoretti, Bruna (Jornal Brasileiro de Economia da Saúde, 2013)
Background: In Brazil, health insurance companies (HIC) must, according to the law, offer coverage for intravenous chemotherapy drugs (IVChem), but not for oral chemotherapy drugs (OChem). We aimed to evaluate the incremental costs and the budgetary impact of the incorporation of OChem, using real world data, from the private payer perspective. Methods: We prospectively collected data during the year of 2008, on chemotherapy usage in 14 HIC, on a population of 2 million people from different regions in Brazil. First we calculated the costs of the IVChem actually used. After that, we indentified which patients would have formal indication for OChem either as a substitutive treatment or in association with IVChem. Then, we calculated the costs associated with this intervention. Later, the budgetary impact of using OChem for the eligible patients was calculated. Only drug acquisition costs were taken into account. We were conservative and assumed a “worst case scenario” approach as the base case, therefore skewing results against OChem. Results: During the one-year period, 1,322 patients that received intravenous chemotherapy also had formal indication to receive OChem. The cost of treatment given to these patients was US 19,630,000. If OChem were also used, the incremental cost would be an additional of approximately US 6,000,000 (US 5,982,656.00) or 30% of the total. The relative incremental cost associated with OChem is therefore US 3.00 per person insured per year or US 0.25 per person insured per month, in a worst case scenario approach. Conclusion: The budgetary impact linked with the adoption of OChem is of US 0.25 per person insured per month, in Brazil, according to this real world data analysis.